Analysis of the Impact of Digital Finance on the Financing Constraints of Small and Medium-Sized Enterprises - Yao, Yang; Wareewanich, Thitinant; Chankoson, Thitinan (Migration Letters, 2024)
High financing constraints hinder the development of SMEs, and digital finance, as a new way to support SME financing, may become an effective means to break through SME financing constraints and reduce financing costs. This paper uses the cross-sectional data of SMEs listed on the SMB from 2011 to 2020 as a sample, and builds an empirical test model based on the cash-cash flow sensitivity model for empirical research. The study shows that digital finance has a significant mitigating effect on the financing constraints of SMEs. In addition, the impact of digital finance on private and high-tech enterprises is greater than that of state-owned enterprises and non-high-tech enterprises. Moreover, the development of digital finance in eastern China can significantly alleviate the degree of financing constraints of SMEs listed on the SME board, while the development of digital finance in central and western China has no significant alleviating effect, showing significant geographical heterogeneity.